Revitalising Agrarian Economies: The Use of Biochar on Banana-based Agroforestry System in Nepal’s hills (Journal of Forest and Livelihood, 2020)
The use of biochar in agroforestry practices is a new concept in Nepal. The soil application of biochar is a promising alternative to increase productivity and reduce chemical fertilizers. To test this concept, an action research project was implemented in two villages of Lamjung district in the middle hills of Nepal. This study aimed at assessing the productivity and livelihood impacts of a banana-based agroforestry system with and without biochar-based fertilization. Biochar was used in one village while another village served as the control (with Nitrogen, Phosphorus, Potassium – NPK application, but no biochar). The information obtained from 111 household surveys was verified and tested through five farmers’ field trials. The paper investigates the effect of different fertilizers on banana yields and its contributions on poverty reduction. The result of the study shows that the banana yield increased by 41 per cent in the plots treated with urine-biochar plus compost compared to the control with conventional NPK fertilization; and more than doubled (102%) compared to the fertilization with compost only. Findings also revealed that the poverty level of respondent households using biochar dropped by 30 percent(from 66% to 36%) in Dhamilikuwa (biochar village) and dropped by 19 per cent (from 40% to 21%) in JitaTaxar (control village). The study implies that the use of biochar in banana-based agroforestry system has the potential for increasing soil productivity and reducing poverty, thereby revitalising agrarian economy of many Nepali villages. A wider replication of this study is therefore recommended, together with enabling public policies to support this practice.